Sistem Informasi Berbasis Web untuk Manajemen Vendor Fotografi Studi Kasus Sincam Photography - Hakim Maulidin, Lutfi Putra; Muchayan, Achmad (Jusikom : Jurnal Sistem Komputer Musirawas, 2024)
The needs of the younger generation who are increasingly independent in wedding planning and the increasing demand for photography services. The development of this system is expected to improve the efficiency and quality of photography services through more structured management. The existence of this research aims to develop a web-based photography vendor management information system for Sincam Photography to overcome challenges in managing vendors and freelancers. Using the waterfall method, this system is designed to simplify the customer booking process and assist management in managing schedules and hiring freelancers. The system has several key features, including complete information about the services offered, activity schedules, and reviews from freelancers. In addition, this system also provides an integrated booking platform and facilitates the recruitment management process and freelancer management. The results of the study show that this web-based photography vendor management information system can help Sincam Photography in optimizing their business management, improving operational efficiency, and providing better services to customers. Thus, this system not only improves the user experience but also supports the growth of Sincam Photography's business.